Long-term retrospective study on the conversion rate from prediabetes to diabetes in transfusion dependent thalassemia (TDT) patients: the experience of a single tertiary care Center in Iran: Thalassemia and conversion rate of prediabetes to diabetes - Saki, Forough; Karimi, Mehran; De Sanctis, Vincenzo; Daar, Shahina; Soliman, Ashraf; Tzoulis, Ploutarchos (Acta Biomedica Atenei Parmensis, 2024)
ackground: The prevalence of glucose dysregulation (GD) in patients with thalassemia increases with age. Objectives: This retrospective study aimed to characterize the natural history of prediabetes and identify risk factors associated with the progression to diabetes among transfusion-dependent thalassemia (TDT) patients. Research Design and Methods: We retrospectively reviewed annual oral glucose tolerance test (OGTT) data from 108 out of 700 Iranian TDT patients diagnosed with diabetes mellitus (DM). Results: Prediabetes was diagnosed at a mean age of 21.3 ± 5.9 years. The mean serum ferritin (SF) level at prediabetes diagnosis was 3,869 ± 2,805 ng/mL. The average time for conversion from prediabetes to DM was 3.8 ± 2.0 years, with a mean age of 25.0 ± 6.5 years at DM diagnosis. A parental history of diabetes was reported in 87% of the patients. There was a direct correlation between the age at prediabetes diagnosis and the age at DM diagnosis (r = 0.9391, P: < 0.00001), as well as with fasting plasma glucose (FPG) at DM diagnosis (r = 0.7065, P: < 0.00001). SF levels at prediabetes diagnosis were also associated with SF levels at the time of DM diagnosis. Conclusions: Identifying high-risk patients remains challenging; however, a parental history of diabetes, elevated SF levels, and younger age at prediabetes diagnosis were significantly associated with the progression to DM in TDT patients with a normal body mass index.